1994
DOI: 10.1017/s0074180900107582
|View full text |Cite
|
Sign up to set email alerts
|

Radio Source Variability as a Tool for Very High Resolution

Abstract: ABSTRACT. If flux density variability is intrinsic to extragalactic sources, then the shortest time scale of the variability yields an extremely high angular resolution. There is, however, good evidence that some of the variability is due to refractive scintillation in our galaxy's interstellar plasma turbulence. The effect, initially discovered at low radio frequencies, is here shown to extend into the GHz band, which, up to now, has been assumed to display only the intrinsic variability. We conclude that fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Since the angular diameter that quenches RISS is substantially larger than for DISS, these authors proposed that RISS could also account for LFV. The suggestion that LFV was due to irregular interstellar propagation had earlier been made by Shapirovskaya (1978), who proposed that refraction in discrete large scale ionized structures was responsible. Several authors (e.g., Rickett 1986;Spangler et al 1993) have since demonstrated that RISS does indeed provide a satisfactory explanation for LFV, based on a power-law model for the spectrum in the interstellar plasma density.…”
Section: Introductionmentioning
confidence: 97%
“…Since the angular diameter that quenches RISS is substantially larger than for DISS, these authors proposed that RISS could also account for LFV. The suggestion that LFV was due to irregular interstellar propagation had earlier been made by Shapirovskaya (1978), who proposed that refraction in discrete large scale ionized structures was responsible. Several authors (e.g., Rickett 1986;Spangler et al 1993) have since demonstrated that RISS does indeed provide a satisfactory explanation for LFV, based on a power-law model for the spectrum in the interstellar plasma density.…”
Section: Introductionmentioning
confidence: 97%
“…Variability at lower frequencies (e.g. Hunstead 1972;Ghosh & Rao 1992) is normally attributed to refractive interstellar scintillation, in which the intensity variations are caused by distortions of the wavefront by electron density gradients in an intervening screen of material (Shapirovskaya 1978;Rickett et al 1984). There is evidence that the parameters of such variability depend on the Galactic latitude of the source (Spangler et al 1989;Ghosh & Rao 1992), suggesting that the material causing the scintillation is in our own Galaxy.…”
Section: Introductionmentioning
confidence: 99%